2011
DOI: 10.3174/ajnr.a2453
|View full text |Cite
|
Sign up to set email alerts
|

Better Outcomes with Treatment by Coiling Relative to Clipping of Unruptured Intracranial Aneurysms in the United States, 2001–2008

Abstract: BACKGROUND AND PURPOSE: Endovascular therapy has increasingly become an acceptable option for treatment of unruptured aneurysms. To better understand the recent trends in the use of and outcomes related to coiling compared with clipping for unruptured aneurysms in the United States, we evaluated the NIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
106
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 20 publications
9
106
2
3
Order By: Relevance
“…38 From this database, morbidity rates ranging from 13.5% to 27.6% and mortality rates ranging from 0.7% to 3.5% have been reported. 2,3,4,5,6,15,18,19,22,28,41 The objective of this institutional review board-approved prospective study was to assess the feasibility and efficacy of the addition of direct neurological testing during both temporary and permanent clipping of UIAs.…”
mentioning
confidence: 99%
“…38 From this database, morbidity rates ranging from 13.5% to 27.6% and mortality rates ranging from 0.7% to 3.5% have been reported. 2,3,4,5,6,15,18,19,22,28,41 The objective of this institutional review board-approved prospective study was to assess the feasibility and efficacy of the addition of direct neurological testing during both temporary and permanent clipping of UIAs.…”
mentioning
confidence: 99%
“…While microsurgical clipping was previously the standard of care, coil embolization has matured rapidly in recent years and is a more frequent treatment alternative with technological advancements and the advent of adjunctive balloon and stent-assisted techniques. 44 Numerous studies have shown a lower periprocedural morbidity and mortality associated with endovascular treatment and lower rates of discharge to long-term care facilities. 44,45 Some authors have suggested that Ͼ90% of aneurysms can now be effectively treated by using endovascular techniques.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…44 Numerous studies have shown a lower periprocedural morbidity and mortality associated with endovascular treatment and lower rates of discharge to long-term care facilities. 44,45 Some authors have suggested that Ͼ90% of aneurysms can now be effectively treated by using endovascular techniques. 46 However, the durability of coil embolization remains frequently debated due to the increased risk of residual aneurysm components or neck remnants, interval rupture or rebleeding (Ͻ1%), and the additional risk of retreatment.…”
Section: Efficacy and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 These articles used the National Inpatient Sample (NIS) data base. This samples one-third of all nonfederal hospital discharges in the United States and is a very powerful tool for examining clinical outcomes; it provides a very large sample size.…”
mentioning
confidence: 99%